The Effect of Zakat Management and the Quality of Zakat Services on Muzzaki Satisfaction in Baznas Jember Regency - Yuliarti, Norita Citra; Sofi, Aulia Firdatus; Nastiti , Ari Sita (Westscience Press, 2024)
This study aims to determine the influence of zakat management and service quality on muzzaki satisfaction in BAZNAS Jember Regency. This study uses a quantitative method sourced from questionnaires. The population of this study is 400 muzzaki. Sampling uses the slovin formula, which is a statistical formula used to determine the minimum number of samples from a limited population (finite population survey). So the number of samples in this study is 80 respondents. The data analysis technique used is the SPSS computer program. The results of this study show that zakat management and service quality have a positive and significant effect on muzzaki satisfaction. Based on the results of the t test, it can be seen that the variable of zakat management is obtained t count > t table (6,965 > 1,991) sig. 0.001 < 0.05 and the variable of service quality was obtained (17.926 > 1.991) sig. 0.001 < 0.05. The result of the determination coefficient (R2) in this study was 0.839 or 83.9%, which means that muzzaki satisfaction was influenced by zakat management and service quality of 83.9%. The results of the multiple linear regression test in the variable of zakat management are 0.387, while for the variable of service quality 0.959, if the coefficient is positive, it means that there is a positive effect between zakat management and service quality on muzzaki satisfaction.